Pengaruh Sumber Pengetahuan Konsumen Non-Business Controlled terhadap Keputusan Penggunaan Direktori Kuliner Online Zomato - Sofia Ramadhani; Ma'mun Sarma (Jurnal Manajemen dan Organisasi, 2018)
The rises of the culinary industry in Indonesia nowadays has opened opportunities for startup developers to create online culinary directories platforms. One of popular online culinary directories or well known by online restaurant searcher in Indonesia is Zomato. To formulate Zomato’s promotional strategies, a study is needed on the sources of knowledge that can not be controlled by the company (non-business controlled). Based on this problem, the aims of this study are to identify the Zomato user characteristics and the relation with Zomato use decisions, to idenitify a relevant consumer sources of knowledge, to analyze it, and, to know its effect on Zomato use decisions. This study uses primary data and secondary data. This study is using logistic regression as analytical model. The result of this study shows that Zomato user is dominated by 16-25 age single woman. Most of them are student and lives in Jakarta. Average income of them are <Rp 2.000.000,- and monthly food expenses in range Rp 500.000,- - Rp 1.000.000,-. The responden using Zomato for looking hangout place or place to eat. The characteristics that affect the Zomato to use decisions are sex and food expenses per month. Logistic regression results at a significant level of 15 percents shows friends, idols, internet forums, bulletin boards, and government publications are the relevant sources of knowledge to the decision for using Zomato. Respondents who strongly agree to know Zomato through friends and government publications tend to use Zomato apps than the other categories. Respondents who know Zomato through idols tend to use apps. Respondents who disagree to know Zomato through internet forums tend to use Zomato website, and respondents who know Zomato through bulletin boards tend to use the Zomato website.